Effects of prehospital 12-lead ECG on processes of care and mortality in acute coronary syndrome: a linked cohort study from the Myocardial Ischaemia National Audit Project. Issue 12 (14th April 2014) - Quinn, Tom; Johnsen, Sigurd; Gale, Chris P; Snooks, Helen; McLean, Scott; Woollard, Malcolm; Weston, Clive; ,
Abstract : Objective: To describe patterns of prehospital ECG (PHECG) use and determine its association with processes and outcomes of care in patients with ST-elevation myocardial infarction (STEMI) and non-STEMI. Methods: Population-based linked cohort study of a national myocardial infarction registry. Results: 288 990 patients were admitted to hospitals via emergency medical services (EMS) between 1 January 2005 and 31 December 2009. PHECG use increased overall (51% vs 64%, adjusted OR (aOR) 2.17, 95% CI 2.12 to 2.22), and in STEMI (64% vs 79%, aOR 2.34, 95% CI 2.25 to 2.44). Patients who received PHECG were younger (71 years vs 74 years, P <0.0001); and less likely to be female (33.1% vs 40.3%, OR 0.87, 95% CI 0.86 to 0.89), or to have comorbidities than those who did not. For STEMI, reperfusion was more frequent in those having PHECG (83.5% vs 74.4%, p<0.0001). PHECG was associated with more primary percutaneous coronary intervention patients achieving call-to-balloon time <90 min (27.9% vs 21.4%, aOR 1.38, 95% CI 1.24 to 1.54) and more patients who received fibrinolytic therapy achieving door-to-needle time <30 min (90.6% vs 83.7%, aOR 2.13, 95% CI 1.91 to 2.38). Patients with PHECG exhibited significantly lower 30-day mortality rates than those who did not (7.4% vs 8.2%, aOR 0.94, 95% CI 0.91 to 0.96). Conclusions: Findings from this national MI registry demonstrate a survival advantage in STEMI and non-STEMI patients when PHECG was used.